Social Context of Face-Threatening Acts in Abu Ubaidah’s Speech on Al Jazeera Channel - Aldrian; Muassomah; Halimi (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
This research examines Face-Threatening Acts (FTAs) in Abu Ubaidah's speech on Al Jazeera's YouTube channel within the context of the Israel-Palestine conflict. Unlike previous studies focused on Western political discourse, this research uncovers distinct face management patterns within Arab-Islamic political communication broadcast globally. Using a qualitative approach with pragmatic discourse analysis, the research analyzes Abu Ubaidah's speech on the Gaza conflict on April 23, 2024. Data collection involved indirect observation through watching and transcribing the speech video, complemented by literature review. The analysis combines Brown and Levinson's politeness model with Miles and Huberman's data reduction, display, and conclusion drawing framework. The findings reveal Abu Ubaidah's strategic use of FTAs for delegitimizing adversaries, constructing resistance identity, and fostering solidarity, with 23 FTAs targeting positive face and 19 targeting negative face. The novelty of this research lies in its focus on the interaction between FTAs and the social context as markers of cultural-religious identity in Arab political discourse during conflicts, and providing new insights into how FTAs is employed to achieve communicative and ideological goals in non-Western contexts. This research recommends further exploring communication strategies in similar conflicts through various linguistic approaches.